Design and environmental sustainability assessment of energy-independent communities: The case study of a livestock farm in the North of Italy. (November 2021) - Maturo, Anthony; Petrucci, Andrea; Forzano, Cesare; Giuzio, Giovanni Francesco; Buonomano, Annamaria; Athienitis, Andreas
Abstract: This paper investigates the energy and economic performance of several energy schemes that could potentially be applied to agricultural and zootechnical communities contributing to the international objectives of sustainable development. The proposed energy schemes involve integrated energy efficiency technologies and novel system layouts aiming at reaching the zero-energy goal at a community level, by considering collective energy actions with provision of benefits for members and stakeholders. The proposed scenarios include different innovative technologies, such as anaerobic digestion, cogeneration, biogas upgrading, solar, district heating and cooling. These layouts are modelled in TRNSYS simulation environment to perform dynamic simulations and parametric analyses of the pivotal system parameters. Such analyses are conducted to find out the best scenario and the size of its system components which optimize different energy and economic objective functions. To assess the feasibility of all proposed scenarios and energy schemes, as well as to investigate the potential of the developed models, proposed scenarios are studied for an existing community. This existing agricultural community named "La Bellotta", is served through different technologies, including a gas fuelled co-generator and an anaerobic biodigester. Simulation results show that the investigated scenarios allow for achieving very high self consumption ratios of energy produced on-site (from 57 to 100%), high economic performance (measured by the profitability index up to 1.35 for the best investigated scenario) and environmental benefits. The case study provides examples of energy schemes in which citizens and communities have a major benefit to invest in projects including renewables technologies, energy efficiency, and positive energy services. Highlights: Achieve zero-energy community goals for livestock farms. Dynamic simulation to improve energy performance. Multi-objective energy optimization for different layout configurations. Model flexibility to enhance universal applicability. Advanced economic analysis to prove the feasibility of investments.